Нові відомості про поширення адвентивного моху Сampylopus introflexus (Hedw.) Brid. (Leucobryaceae) в Україні - Кузярін, О.Т. (Український ботанічний журнал, 2012)
Приведены новые сведения о распространении адвентивного мха-неофита Сampylopus introflexus
(Hedw.) Brid. в Украине. Сообщается о находке двух новых локалитетов вида (в июне
2009 г. и в сентябре 2011 г.) на торфокарьерах Львовской области. Дана характеристика его
новых местонахождений. Выяснены эколого-фитоценотические условия, динамические тенденции и факторы, лимитирующие распространение С. introflexus в Украине. New data on the occurrence of the alien moss, neophytic Сampylopus introflexus (Hedw.) Brid., in
Ukraine is recorded. Two new habitats of the species were discovered in June 2009 and September
2011 during surveys on the peateries of Lviv Region. Characteristics of the two new habitats of the
species are given. The ecological phytocoenotic conditions, dynamic tendencies and limiting factors
of С. introflexus distribution in Ukraine are discussed.